The Effectiveness of the District Health Board Development Model in Samut Sakhon Province - Lamsakorn, Sorachai (Journal of Preventive Medicine Association of Thailand, 2024)
Objective: The objectives were to 1) study the situation and problem conditions of operations to develop the quality of life at the district level of Krathum Baen District 2) develop a model of operations to develop the quality of life at the district level of Krathum Baen District and 3) study the effectiveness of operations to develop the quality of life at the district level of Krathum Baen District. Methods: This research was participatory action research. The sample group was the District Quality of Life Development Committee representatives of government agencies, the private sector, and the public sector, totaling 49 people. The tools used were interviews and performance evaluation forms according to UCCARE criteria. Data was collected through focus groups and in-depth interviews. Quantitative data were analyzed using descriptive statistics, and qualitative data used content analysis. Results: The results of the research found that 1) The problem conditions found were: The committee lacks understanding of its roles and responsibilities, budget allocation is not consistent with the problem, and data management is inefficient 2) The format developed was to appoint committees from all sectors to jointly think, plan, develop, solve problems and receive benefits. Strategy in 4 areas: waste management, care for chronic non-communicable diseases, communicable diseases, and socially vulnerable people, and 3) the results of the evaluation according to the UCCARE criteria, passing the level 5 evaluation in all areas, tend to improve, and able to solve problems effectively. Conclusion: The DHB establishes channels to receive necessary information or issues from the community, to collectively determine appropriate strategies for improving the quality of life for the people, and to derive genuine benefits. Additionally, opportunities were provided for civil society to take the lead in problem-solving efforts and foster genuine participation.